STUNTING PREVENTION "SMART GUIDANCE MODULE AND REAL ACTION" IN CADRES, ADOLESCENTS, PREMARRIED AND PREGNANT WOMEN - Krisdiana Wijayanti; Sri Wahyuni; Rafika Fajrin; Heny Rosiana; Yuwono Setiadi (Wealth Community Empowerment, 2025)
Indonesia is currently facing a "double burden of malnutrition" or double nutritional problems where on the one hand it still has to work hard to overcome the problem of malnutrition, one of which is stunting, while on the other hand the problem of excess nutrition is starting to creep up which leads to an increase in cases of non-communicable diseases (NCDs) in the adult group. The objectives to be achieved in this activity are: Identifying the knowledge of adolescents, pre-marital, and identifying the knowledge of pregnant women about preventing stunting in toddlers, providing knowledge of pregnant women about preventing stunting in toddlers. The solution provided in dealing with these problems is by providing assistance in providing education as a guide for cadres, pregnant women, adolescents and pre-marital in preventing stunting using the Smart Guidance Module and Real Action. The smart guidance module in this community service is compiled as a reference in carrying out real actions to prevent stunting through real action. The methods of this community service are lectures, discussions, and direct practice. The results of community service obtained an average target knowledge, namely cadres, pregnant women, adolescents and pre-marital, increased. It is hoped that after community service, all parties can work together in stunting convergence